(3MdjI GdCHQGQ hTYGQ GdCNjGQ aj GdCPcGQ GdeSJMSfI BfGA Gddjd hCWQGa GdfgGQs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3CMeO Hf eMeO Hf YHO GdgGOi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ , GdYRjR GdZaGQ CeG HYO , abO bGd Gddg GdYXje GdYRjR GdMcje aGPcQhfi CPcQce , hbGd JYGdi , heG NdbJ GdLf hGdCfS EdG djYHOhf s
(3BNQgG (B:s
,(3SGJhOY Gddg GdcQje GddWja GdQMje efi hef hGdOi hLjeY CMHGHfG hENhGffG hef CMSf EdjfG bGd eUfag aQZJ ef LeYg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG ahGFO hJYdjbGJs
(3hcJH HYV GdYfGhjjf HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs